Study of Sedative and Anxiolytic Effect of Herbal Extract of Nardostachys jatamansi in Comparison With Diazepam in Rats - A Rezaie; M Pashazadeh; Ch Ahmadizadeh; B Jafari; HM Jalilzadeh (Institue of Medicinal Plants, ACECR, 2010)
Background: Due to sedation, anticonvulsant and anti-pain effects, Nardostachys jatamansi has had a special place in traditional medicine of China, India and Iran. Regarding Alkaloid, Organic acid esters, valeric acid and isovalerates this plant has always been used to reduce nervous pressure and the treatment depression and chronic insomnia. Objective: Considering the importance of sedative and anxiolytic effects of this plantchr('39')s we decided to have a comparative study of this plant with chemical drugs. Methods: In this study, first, the rhizome of N. jatamansi was extracted by hydromethanolic (70%) solvent and then, the presence of valporoates, in total extract was revealed by GC-MS analysis of its n-Hexane fraction. For studying the effectiveness of sedative and anxiolytic of N. jatamansi in compraison with diazepam different groups of female wistar rats received N. jatamansi (100, 200, 400 mg/kg, ip), diazepam (1.2 mg/kg, ip), di-metyl solphoxid (DMSO) with equal volume, and 15 min after assessing the relif/sleep inducing effect (induced sleep duration by ketamine, 40 mg/kg, ip) and anxiolytic effects (using Elevated plus were done). Results: The GC-MS analysis of the n-hexan fraction of extract led to identification and quantification of fifteen compounds, the main components were a - Aristolen-1-alpha-ol (31.1%), valerenal (31%) and valerenic acid (26.5%). Pharmacological results showed that herbal extract of N. jatamansi with the maximum inhibition was observed at the does of 200 mg/kg of sedative and anxiolytic effect. Conclusion: Obtained resultes indicated that extract of N. jatamansi gives sedative and anxiolytic effects.